Efficient adaptive sampling applied to multivariate, multiple output rational interpolation models, with applications in electromagnetics-based device modelling - Lehmensiek, Robert (Stellenbosch : Stellenbosch University, 2011)
Thesis (PhD) -- Stellenbosch University, 2001.